ROTA CRÍTICA DE MULHERES EM SITUAÇÃO DE VIOLÊNCIA INTRAFAMILIAR NO MUNICÍPIO DE PONTA GROSSA/PR E O TRABALHO EM REDE - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2013)
This dissertation has as subject the network of care to women in situations of intrafamily violence in the Ponta Grossa city, state of Paraná. The aims, in general, are check critical routes of women in situations of intrafamily violence, in other words, the way taken by these women with some representative organs from each segment that looks after these women in this city. The specific objectives are see how these care services are structured care services;describe the path taken by women when looking for guarantee their rights and check for the exercise of intersectoral between organizations and how they are articulating for treatment effective of women who seek the services. To achieve these goals, some theoretical and historical issues were worked. At first deal about gender and feminism and the changes in consequence of about by the feminist movement. In a second moment, we treat the issue about violence against women and Law nº 11.340/2006 (Maria da Penha Law), withan emphasis on the legal advances and the formulation of policies for women in this situation. In the third stage, treated networking by discussing the challenges and importance of a service network addressing the reality of the Ponta Grossa city. Through the analysis of interviews with professionals and women victims of violence and the data collected, it was to analyzed the critical route and the coordination of services in the city. The research was qualitative relying on quantitative data, and we used the following methodological: literature, documents and semi-structured interviews, and for the data analysis, used the content analysis.
Keywords: violência intrafamiliar; rota crítica; rede intersetorial; intrafamily violence; critical route; intersectoral network; CNPQ::CIENCIAS SOCIAIS APLICADAS